International Trade Patterns and Labor Markets – An Empirical Analysis for EU Member States - Götz Zeddies (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2010)
During the last decades, international trade flows especially of the industrialized countries allegedly became more and more intra-industry. At the same time, employment perspectives particularly of the low-skilled by tendency deteriorated in these countries. This phenomenon is often traced back to the fact that intra-industry trade, which should theoretically involve low labor market adjustment, became increasingly vertical in nature and might thus entail labor market disruptions. Against this background, the present paper investigates the relationship between international trade patterns and selected labor market indicators in European countries, with a focus on vertical intra-industry trade. As the results show, neither inter- nor vertical intra-industry trade do have a verifiable effect on wage spread in EU member states. As far as structural unemployment is concerned, the latter increases only with the degree of countries' specialization on capital intensively manufactured products in inter-industry trade relations. Only for unemployment of the less-skilled, a significant impact of superior vertical intra-industry trade seems to exist. However, the link between unemployment of the lower qualified and inter-industry specialization on labor intensive goods as well as parts and components imports is considerably higher. – – In den zurückliegenden Jahrzehnten waren die internationalen Handelsmuster grundlegenden Veränderungen unterworfen. Insbesondere in den Industrieländern gewann der intra-industrielle Handel zusehends an Bedeutung. Gleichzeitig verschlechterten sich in diesen Ländern die Beschäftigungsaussichten gering qualifizierter Arbeitskräfte. Diese Entwicklung wird häufig der Tatsache zugeschrieben, dass der intra-industrielle Handel zunehmend vertikaler Natur ist und damit, ähnlich wie der inter-industrielle Handel, mit Rückwirkungen auf die Faktormärkte verbunden sein kann. Vor diesem Hintergrund untersucht die vorliegende Studie die Wechselwirkungen zwischen internationalen Handelsmustern und ausgewählten Arbeitsmarktindikatoren europäischer Länder. Der Fokus liegt dabei auf dem vertikalen intra-industriellen Handel. Im Ergebnis zeigt sich, dass weder vom inter- noch vom vertikalen intra-industriellen Handel Rückwirkungen auf die Lohnspreizung in den EU-Mitgliedstaaten ausgehen. Die strukturelle Arbeitslosigkeit wird zwar über die Spezialisierungsmuster der Länder im inter-industriellen, nicht aber im vertikalen intra-industriellen Handel erklärt. Lediglich zwischen der Arbeitslosigkeit gering Qualifizierter und dem vertikalen intra-industriellen Handel besteht ein signifikanter Zusammenhang.
urn:nbn:de:101:1-20100706126
Keywords: F12; F16; J64; 330; intra-industry trade; trade and labor market interactions; unemployment; intra-industrieller Handel; internationaler Handel und Arbeitsmärkte; Arbeitslosigkeit; Außenhandelsstruktur; Intraindustrieller Handel; Lieferanten-Kunden-Beziehung; Beschäftigungseffekt; Lohnstruktur; Arbeitslosigkeit; Ungelernte Arbeitskräfte; EU-Staaten